Russ Parsons: How to Read a French Fry - Davidson, Alan (Petits Propos Culinaires, 2024)
Russ Parsons: How to Read a French Fry: Houghton Mifflin, New York, 2001: ISBN 0-395-96783-X: 334 pp., h/b, 25.00.